Anaerobic Co-Digestion of Cattle Manure with Ruminal Waste to Increase Biogas Production - Fatih Şevki Erkuş; Koray Tuncay (Turkish Journal of Agriculture: Food Science and Technology)
Cattle manure (CM) is mostly used as an inoculum in order to start-up of agricultural biogas plants or as a co-substrate in the anaerobic digestion of lignocellulosic content. Rumen fluid microbiota is also considered to be effective in lignocellulose digestion. It is known that microorganisms in the ruminal waste facilitate the hydrolysis of lignocellulosic structures. However, there are few studies on the inoculum effect of rumen microorganisms on bioreactor performances when rumen content is used as co-substrate and inoculum together with cattle manure, and it is not clear how rumen waste can be used in various anaerobic digestion systems. In this study, biogas production efficiencies obtained from lignocellulosic content in mono and cosubstrate (1:1 and 1:2 Volatile Solids) bioreactors formed by using ruminal waste (RW) and CM microbial communities were investigated. In order to determine the biogas production efficiencies, biomethane potential (BMP) experiments that simulate anaerobic digestion process conditions in a laboratory environment were applied. Treatment with 50% application of RW cosubstrate, 65.51% biogas and 70.64% methane production efficiency increases were achieved compared to monosubstrate CM bioreactor.